Implementasi Kebijakan dalam Kegiatan Pemenuhan Hak Kesejahteraan Sosial Penyandang Disabilitas Dinas Sosial di Desa Rowosari Kecamatan Tembalang Kota Semarang Tahun 2022 - Suharto, Suharto; Jifhani, Reni (Universitas Wahid Hasyim Semarang, 2024)
Penelitian ini bertujuan untuk mengetahui pelaksanaan kegiatan pemenuhan hak kesejahteraan sosial di Desa Rowosari Kecamatan Tembalang Kota Seamarang dan mengetahui faktor pendukung serta penghambatnya. Teori yang digunakan untuk mendukung implementasi pemenuhan hak kesejahteraan ini yaitu model implementasi kebijakan yang dikembangkan oleh Edward III yaitu komunikasi, sumberdaya, sikap pelaksana dan struktur birokrasi. Metode penelitian yang digunakan adalah metode deskriptif dengan pendekatan kualitatif. Teknik yang digunakan untuk pengumpulan data yaitu wawancara, observasi, dan dokumentasi. Kesimpulan penelitian ini bahwa implementasi kebijakan tersebut sudah berjalan dengan baik namun masih terdapat beberapa kekurangan, yaitu komunikasi yang kurang menyeluruh pada masyarakat, kurangnya pemerataan sosialisasi dari pihak pelaksana kepada masyarakat, kurangnya tenaga pengajar pendidik dan juga wawasan terkait dengan IT, kemudian kurangnya alat pendukung seperti kursi roda, alat transportasi, bangunan yang belum ramah difabel, dan tidak adanya bangunan tempat belajar khusus difabel di desa Rowosari.Kata Kunci: Implementasi Kebijakan Publik, Kesejahteraan Sosial, Penyandang DisabilitasABSTRACTImplementation of public policy is an action carried out by individuals or groups in the government and private sector which is directed at achieving the goals set in policy decisions. Social Welfare is a condition that must be realized for all citizens in fulfilling material, spiritual and social needs so that they can live a decent life and be able to develop themselves, so that they can carry out their social functions. Persons with disabilities are classified as part of society who have a life that is not worthy of humanity and have criteria for social problems. implementing a program of social welfare activities, namely by carrying out activities to fulfill social welfare rights for persons with disabilitiesThis research aims to determine the implementation of activities to fulfill social welfare rights in Rowosari Village, Tembalang District, Seamarang City and determine the supporting and inhibiting factors. The theory used to support the implementation of fulfilling welfare rights is the policy implementation model developed by Edward III, namely communication, resources, attitude of implementers and bureaucratic structure. The research method used is a descriptive method with a qualitative approach. The techniques used for data collection are interviews, observation and documentation. The conclusion of this research is that the implementation of the policy has gone well but there are still several shortcomings, namely less comprehensive communication with the community, lack of even distribution of socialization from the implementer to the community, lack of teaching staff and also insight related to IT, then lack of supporting tools such as wheelchairs, means of transportation, buildings that are not disabled-friendly, and there are no buildings specifically for disabled learning in Rowosari village.Keywords: Public Policy Implementation, Social Welfare, Persons with Disabilities